A Comparative Study of Interdisciplinary Field of Culture and Communication in Canada and USA - Mahdi Zolfaghari; Mhammad Mohsen Hassanpour; Mehdi Shahin (Comparative Education Society of Iran ( CESIR), 2019)
The field of interdisciplinary studies is a relatively new field in academic approaches. The interdisciplinary studies have been considered due to the increasing complexity of social problems, the need for combined approaches and the adoption of multiple approaches in order to address scientific problems. The present study, with a qualitative approach and thematic analysis, will extract information on the history, fields and approaches at five universities and more than 25 interdisciplinary courses in the field of media studies, culture and communication. The study results show that simultaneous attention to the "structural" and "content" characteristics is essential to the success of the interdisciplinary courses. The study results showed that structurally, small group training and the use of four semester teaching method increase the efficiency of interdisciplinary courses. Also, consideration of content characteristics such as setting goals, allocating interdisciplinary courses to graduate students, and increasing the number of selective courses should be observed by Iranian higher education policy makers.